Biomechanical Comparison Between Porous Ti6Al4V Block and Tumor Prosthesis UHMWPE Block for the Treatment of Distal Femur Bone Defects - Zhang, Jiangbo; Liu, Yang; Han, Qing; Zhang, Aobo; Chen, Hao; Ma, Mingyue; Li, Yongyue; Chen, Bingpeng; Wang, Jincheng (Frontiers in Bioengineering and Biotechnology, 2022)
Purpose: The management of bone defects is a crucial content of total knee revision. This study compared the biomechanical performance of porous Ti6Al4V block and tumor prosthesis UHMWPE block in treating distal femoral bone defects. Methods: The finite element models of AORI type 3 distal femoral bone defect treated with porous Ti6Al4V block and UHMWPE block were established. Sensitivity analysis was performed to obtain the appropriate mesh size. The biomechanical performance of treatment methods in bone defects were evaluated according to the peak stress, the Von Mises stress distribution, and the average stresses of regions of interest under the condition of standing on one foot and flexion of the knee. Statistical analysis was conducted by independent samples t-test in SPSS (p＜0.05). Results: In the standing on one-foot state, the peak stress of the porous Ti6Al4V block was 12.42 MPa and that of the UHMWPE block was 19.97 MPa, which is close to its yield stress (21 MPa). Meanwhile, the stress distribution of the UHMWPE block was uneven. In the flexion state, the peak stress of the porous Ti6Al4V block was 16.28 MPa, while that of the UHMWPE block was 14.82 MPa. The average stress of the regions of interest in UHMWPE block was higher than that of the porous Ti6Al4V block in both states (p＜0.05). Conclusion: More uniform stress distribution was identified in the porous Ti6Al4V block application which could reserve more bone. On the contrary, uneven stress distribution and a larger high-stress concentration area were found in the UHMWPE block. Hence, the porous Ti6Al4V block is recommended for the treatment of AORI type 3 distal femoral bone defect.